ІНТЕЛІГЕНЦІЯ РЕГІОНУ ЦЕНТРАЛЬНО-СХІДНОЇ ЄВРОПИ В 70–80-ті рр. XX ст.: ГЕНЕЗА ОПОЗИЦІЙНОСТІ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of both function and place of Central Eastern Europe region intelligentsia in the oppositional movement of 1970th-1980th. The backgrounds of intelligentsia’s turning into a subject of transformational processes are investigated, the genesis of oppositional spirits in this social group in times of Gorbachov’s reformation are characterized. The author emphasizes, that the scales and the effectiveness of intelligentsia’s participation in social and political transformation in each country of the region was defined by the historical heritage, by traditions of political culture, by the specificity of governmental systems and so on.